Tematska stičišča pisateljic Zofke Kveder in Julke Hlapec Đorđević - Fužir, Barbara (Jezik in slovstvo, 2011)
In addition to stylistic and conceptual-thematic similarities, the novel Hanka(1918) by Slovene writer Zofka Kveder and the novel Jedno dopisivanje - fragmenti romana (1932) by Serbian writer Julka Hlapec Đorđević are also linked by the authors' similar international paths and their interest in the woman question, which, in spite of numerous similarities in the selected works, in places also led to different findings. Both writers presented the figure of the female intellectual. In Hanka, the female intellectual delves into her own intimacy and attempts to solve her inner conflicts, while in Jedno dopisivanje the figure of the female intellectual is presented as the antipole to the emotional male subject. The novel by the Serbian writer is also interesting due to the inclusion of the figure of Zofka Kveder in the plot itself.
Keywords: Kveder, Zofka, 1878-1926; Hlapec Đorđević, Julka, 1881-1969; Slovene literature; slovenska književnost; srbska književnost; romani; primerjalne študije; Kveder, Zofka: Hanka; Hlapec Đorđević, Julka: Jedno dopisivanje - fragmenti romana